Photoreceptor glucose metabolism determines normal retinal vascular growth. Issue 1 (27th November 2017) - Fu, Zhongjie; Löfqvist, Chatarina A; Liegl, Raffael; Wang, Zhongxiao; Sun, Ye; Gong, Yan; Liu, Chi‐Hsiu; Meng, Steven S; Burnim, Samuel B; Arellano, Ivana; Chouinard, My T; Duran, Rubi; et al.
Abstract: The neural cells and factors determining normal vascular growth are not well defined even though vision‐threatening neovessel growth, a major cause of blindness in retinopathy of prematurity (ROP) (and diabetic retinopathy), is driven by delayed normal vascular growth. We here examined whether hyperglycemia and low adiponectin (APN) levels delayed normal retinal vascularization, driven primarily by dysregulated photoreceptor metabolism. In premature infants, low APN levels correlated with hyperglycemia and delayed retinal vascular formation. Experimentally in a neonatal mouse model of postnatal hyperglycemia modeling early ROP, hyperglycemia caused photoreceptor dysfunction and delayed neurovascular maturation associated with changes in the APN pathway; recombinant mouse APN or APN receptor agonist AdipoRon treatment normalized vascular growth. APN deficiency decreased retinal mitochondrial metabolic enzyme levels particularly in photoreceptors, suppressed retinal vascular development, and decreased photoreceptor platelet‐derived growth factor ( Pdgfb ). APN pathway activation reversed these effects. Blockade of mitochondrial respiration abolished AdipoRon‐induced Pdgfb increase in photoreceptors. Photoreceptor knockdown of Pdgfb delayed retinal vascular formation. Stimulation of the APN pathway might prevent hyperglycemia‐associated retinal abnormalities and suppress phase I ROP in premature infants. Synopsis: Hyperglycemia and low circulating adiponectin (APN) levels are understudied risk factors for retinopathy of prematurity. A mouse model of hyperglycemia‐associated retinopathy reveals that APN restores hyperglycemia‐associated photoreceptor dysfunction and promotes retinal vessel growth. Clinically, in very preterm infants, low circulating APN levels are associated with hyperglycemia and delayed normal retinal vascularization. Photoreceptor metabolism determines normal vascular development. Hyperglycemia delays normal retinal vascular growth in a newly established neonatal mouse model of hyperglycemic retinopathy of prematurity. APN deficiency suppresses and activation of the APN pathway normalizes photoreceptor metabolism and retinal vascularization. A new therapeutic intervention (stimulation of the APN pathway) at early stages may improve hyperglycemia‐associated retinal neurovascular disorders like retinopathy of prematurity in preterm infants with implications for diabetic retinopathy in adults. Abstract : Hyperglycemia and low circulating adiponectin (APN) levels are understudied risk factors for retinopathy of prematurity. A mouse model of hyperglycemia‐associated retinopathy reveals that APN restores hyperglycemia‐associated photoreceptor dysfunction and promotes retinal vessel growth.